2013
DOI: 10.1111/gfs.12096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of population combinations on the reproductive success and germination of seeds of Bromus auleticus (Poaceae)

Abstract: Bromus auleticus is known for its qualities as forage but its domestication has limitations relating to seed production technology and farm‐scale seed propagation. The effect of different combinations of population on the reproductive success and seed germination of a relict population of Argentina was studied. The tests used a population of Santa Fe (SF) as the recipient of pollen and three populations as donors (LP: La Pampa, ER: Entre Ríos and BA: Buenos Aires). Reproductive success was determined in plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…B. auleticus Trinius ex Nees is a C3 perennial grass, native to Rio de la Plata grasslands, including central east of Argentina, Uruguay and south of Brazil (Gutiérrez & Pensiero, 1998). Phenotypic characterisation of plants from different accessions suggests the existence of ecotypes with specific adaptations to local environmental conditions (Condón et al, 2017; Gutiérrez et al, 2006, 2015). In this article, we worked with two Argentinean ecotypes that in accordance with the collection site, we named La Pampa (LP) and El Palmar (EP).…”
Section: Methodsmentioning
confidence: 99%
“…B. auleticus Trinius ex Nees is a C3 perennial grass, native to Rio de la Plata grasslands, including central east of Argentina, Uruguay and south of Brazil (Gutiérrez & Pensiero, 1998). Phenotypic characterisation of plants from different accessions suggests the existence of ecotypes with specific adaptations to local environmental conditions (Condón et al, 2017; Gutiérrez et al, 2006, 2015). In this article, we worked with two Argentinean ecotypes that in accordance with the collection site, we named La Pampa (LP) and El Palmar (EP).…”
Section: Methodsmentioning
confidence: 99%
“…Las prácticas de manejo diseñadas para mejorar la oferta forrajera para la alimentación del venado de las pampas resultaron exitosas. Además, la aparición y el incremento de la cobertura de Elymus scabrifolius tanto en los montes de tala como en el espartillar, y el de Bromus auleticus en el monte de tala, son procesos muy alentadores para los objetivos de conservación de la flora nativa del Parque Nacional Campos del Tuyú ya que Elymus scabrifolius ha sido considerada en inminente peligro de extinción (Andrés 1986, citado en Abala et al 2009, mientras que Bromus auleticus se encuentra en una forma fragmentada en la región central (Gutiérrez and Pensionar 2012), con algunas poblaciones sometidas a un proceso de reducción drástica de tamaño debido a la acción antrópica (Gutiérrez et al 2013).…”
Section: D��������unclassified
“…Biological treatment methods include treating seeds with fungi, bacteria, plant products, or exogenous hormones. Some studies have found that the mechanism of growth-promoting microorganisms primarily involves improving the ability of rhizosphere colonization to produce antibiotics and phytohormones; this promotes signal transduction, gene expression, chlorophyll synthesis, and rhizosphere growth, ultimately inducing plant resistance and promoting growth and yield (Gutiérrez et al, 2015). Compared to the possible harm that chemical treatment can inflict on the environment and the longer time periods required for biological treatment, physical treatment is more advantageous.…”
Section: Introductionmentioning
confidence: 99%